2009
DOI: 10.1038/icb.2009.45
|View full text |Cite
|
Sign up to set email alerts
|

Why is effective treatment of asthma so difficult? An integrated systems biology hypothesis of asthma

Abstract: A hypothesis is presented that asthma is not only an airway disease, but that the disease involves the entire lung, and that the chronicity of asthma and asthma exacerbations can perhaps be explained if one considers asthma as a systemic disease. Increased lung-not only airway-vascularity may be the result of the action of angiogenesis factors, such as vascular endothelial growth factor (VEGF) and sphingosine-1-phosphate (S1P). A bone-marrow lung axis can be postulated as one element of the systemic nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 103 publications
0
4
0
1
Order By: Relevance
“…Extrusion is critical for maintaining proper epithelial barrier function; therefore, we expect defects in the S1P 2 signaling pathway may result in diseases associated with poor mucosal barriers. Aberrant levels of S1P have been associated with asthma, which many believe may initiate from poor barrier function in airway epithelia ( Gitter et al, 2001 ; Proksch et al, 2006 ; Sartor, 2006 ; Kim et al, 2009 ; Swindle et al, 2009 ; Voelkel and Spiegel, 2009 ). Further, aberrant S1P signaling is known to be involved in a variety of pathways that could further aggravate asthma, including immune cell migration ( Matloubian et al, 2004 ; Gude et al, 2008 ; Weigert et al, 2009 ), epithelial proliferation ( Shida et al, 2008 ), and vasoconstriction ( Watterson et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Extrusion is critical for maintaining proper epithelial barrier function; therefore, we expect defects in the S1P 2 signaling pathway may result in diseases associated with poor mucosal barriers. Aberrant levels of S1P have been associated with asthma, which many believe may initiate from poor barrier function in airway epithelia ( Gitter et al, 2001 ; Proksch et al, 2006 ; Sartor, 2006 ; Kim et al, 2009 ; Swindle et al, 2009 ; Voelkel and Spiegel, 2009 ). Further, aberrant S1P signaling is known to be involved in a variety of pathways that could further aggravate asthma, including immune cell migration ( Matloubian et al, 2004 ; Gude et al, 2008 ; Weigert et al, 2009 ), epithelial proliferation ( Shida et al, 2008 ), and vasoconstriction ( Watterson et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the DE genes identified can serve as a valuable source of potential therapeutic targets in the treatment of equine RAO and human asthma. The HIF-1α subunit has been already proposed as a therapeutic target in asthma [ 112 ] and effectiveness of HIF-1 inhibitors in reducing the symptoms of allergic rhinitis has been reported in mouse models [ 113 ]. Also, CXCL13 , which was significantly upregulated in RAO samples upon stimulation with LPS/HDE, has been recently proposed as a target gene in asthma treatment based on experiments performed in a mouse asthma model [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence the study of MRPL4, BCAP other molecules involved in the HIF-1α and PI3K/Akt signaling pathways might help understand the pathophysiology of allergic rhinitis and other atopic phenotypes. Recent research has also shown promise of therapeutic intervention of the HIF-1α as well PI3K/Akt signaling pathways for treatment of asthma and other related allergic conditions [57] , [58] , [59] .…”
Section: Discussionmentioning
confidence: 99%